Simultaneous measurement of strain and temperature using the first- and second-order diffraction wavelengths of bragg gratings - Kalli, Kyriacos; Jackson, David A.; Webb, David J.; Brady, Garret P.; Reekie, Laurence; Archambault, Jean Luc (My University, 1997)
A method of discriminating between temperature and strain effects in fibre sensing using a conventionally written, in-fibre Bragg grating is presented. The technique uses wavelength information from the first and second diffraction orders of the grating element to determine the wavelength dependent strain and temperature coefficients, from which independent temperature and strain measurements can be made. The authors present results that validate this matrix inversion technique and quantify the strain and temperature errors which can arise for a given uncertainty in the measurement of the reflected wavelength
Keywords: Diffraction gratings; Temperature measurements; Fiber optics; Bragg gratings